Back Cover: A novel urine analysis technique combining affinity chromatography with Au nanoparticle based surface enhanced Raman spectroscopy for potential applications in non‐invasive cancer screening (J. Biophotonics 4/2019). Issue 4 (2nd April 2019) - Unknown
Abstract : A novel urine analysis technique combining affinity chromatography with Au nanoparticle‐based SERS spectroscopy for potential applications in noninvasive gastric cancer and breast cancer screening. Both the gastric cancer and the breast cancer group can be discriminated from the normal group using SERS spectroscopy combined multivariate diagnostic algorithm, leading to high diagnostic accuracy. These results demonstrate that the urine analysis method has great potential for cancer detection in liquid biopsies. Further details can be found in the article by Xueliang Lin, Lingna Wang, Huijing Lin, et al. (e201800327 ). Abstract : A novel urine analysis technique combining affinity chromatography with Au nanoparticle‐based SERS spectroscopy for potential applications in noninvasive gastric cancer and breast cancer screening. Both the gastric cancer and the breast cancer group can be discriminated from the normal group using SERS spectroscopy combined multivariate diagnostic algorithm, leading to high diagnostic accuracy. These results demonstrate that the urine analysis method has great potential for cancer detection in liquid biopsies. Further details can be found in the article by Xueliang Lin, Lingna Wang, Huijing Lin, et al. (e201800327 ).